PENGARUH MOTIVASI KERJA TERHADAP KINERJA PEGAWAI PADA KANTOR BADAN KEPEGAWAIAN DAERAH PROVINSI JAMBI - Saiyid Syekh; Ahmad Firdaus (Eksis: Jurnal Ilmiah Ekonomi dan Bisnis, 2015)
Management is a process that consists of the function of planning, organizing, leadership and control of the activities of human resources and other resources to achieve the stated goals efficiently. From the hypotesis testing results it can be concluded that motivation variable (X) is able to explain the variable (Y) or the performance of employees is 96,6% and 78,2% otherwise be caused by other variables outside variables studied. From the opinions of expert who address of management it can be concluded that management isa process of planning, organizing, leadership, and control of the activities of human resources to achieve the goals that have been set together. In this study there are indicators of some motivational variables variables IE. Physiological needs, safety needs, the needs of the award, the needs of larger groups, the need for self-actualization. While performance indicators covering quality, quantity, timeliness, effectiveness, independence. Staffing Agency area of Jambi province was formed based on the applicable local Jambi province number 15 in 2008, as it transformed into a Regional Regulation number 6, 2010 about the Organization and the Labor Inspectorate, the regional development planning board and Technical Institutions of the regional province of Jambi. Based on a regression equation to calculate simple linear, obtained the following mathematical equation Y = 1,658 + 0484 X from the following equation looks positive impact of motivation on performance of employees in the Agency's staffing area of Jambi province. If motivation increase 100% the performance of employees in the Agency's staffing area of Jambi province will be increased by 48.4%. This fact shows that motivation affect performance in Staffing Agency area of Jambi province. Motivation in the staffing Agency area of Jambi province high with an average score of 343.4 while the Staffing Agency's performance in the area of Jambi province high with an average score of 346.13 which means that the hypothesis of work motivation and performance of the Agency's Regional Staffing officer province of Jambi.Keyword: work motivation, employee performance